The increase of uncoupling protein-1 expression after moderate intensity continuous exercises in obese females - Sugiharto; Sakti Adji, Banih; Merawati, Desiana; Pranoto, Adi (Universitas Nusantara PGRI Kediri, 2021)
This study aims to prove an increase in the expression of uncoupling protein-1 (UCP-1) after moderate-intensity continuous exercise in obese females. The present study employed a true-experimental with the randomized control group pretest-posttest design. A total of 12 obese females were enrolled in this study and given moderate-intensity continuous exercise. Continuous exercise was done with an intensity of 60-70% HRmax for 40 minutes using a treadmill. The Enzyme-Linked Immunosorbent Assay (ELISA) method was used to examine the expression of UCP-1. Data were analyzed using independent samples t-test with statistics packet for social science (SPSS) software version 17. The results obtained mean UCP-1 expression on K1 between pre-exercise (3.68±0.46) ng/mL, post-exercise (3.73±0.69) ng/mL and (p=0.875). Mean UCP-1 expression on K2 between pre-exercise (3.64±1.52) ng/mL, post-exercise (6.83±0.64) ng/mL and (p=0.001). Based on the results of the study, it can be concluded that there is an increase in UCP-1 expression between before and after moderate-intensity continuous exercise in obese females. Future studies are suggested to compare the effect of acute exercise with moderate intensity chronic exercise on increasing UCP-1 expression in obese females.